Hormone-dependent cancer and adverse reproductive outcomes in farmers' families - effects of climatic conditions favoring fungal growth in grain - Kristensen, Petter; Andersen, Aage; Irgens, Lorantz M (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'The impact of grain farming and climate on late-term abortion among female farmers, male genital birth defects among their sons, and hormone-dependent cancer among male and female farmers and their adult children was investigated.' ' METHODS ': 'National registers were cross-matched in Norway and 246 043 male and female farmers born in 1925-1971 were identified, as were their 264 262 children, born in 1952-1980, in agricultural censuses and in the population register. The subjects were followed in the Cancer Register through 1995. Farmers' births, conceived in 1973-1991, were identified, and the prevalences of late-term abortion in mothers and hypospadias and cryptorchidism in their sons at birth were examined. Exposure, defined as the combination of grain farming and categories of seasonal or cumulative warnings, was based on data in agricultural censuses and on local, seasonal, field fungal warnings. Estimated adjusted rate ratios or prevalence ratios served as the measures of association.' ' RESULTS ': 'Categories of high exposure were associated with reproductive outcomes and cancer among female farmers, the strongest occurring for late-term abortion (ratio 2.6, 95% confidence interval (95% CI) 1.6-4.3). Exposure associations for ovarian and breast cancer, and male genital defects, were more moderate. Endometrial cancer was associated with grain farming (ratio 2.0, 95% CI 1.4-2.8) across all levels of fungal warnings. Exposure associations for cancer were strongest for premenopausal, parous women. Exposure was not associated with cancer among male farmers or children.' ' CONCLUSIONS ': 'Climatic conditions favoring fungal growth in grain were associated with hormone-dependent adverse outcomes among female farmers; the results are consistent with hormonal effects of inhaled mycotoxins during pregnancy.
Keywords: breast cancer; climatic conditions; cryptorchidism; endometrial cancer; farmer’s family; fungal growth; grain; hormone-dependent cancer; hypospadias; male; mediated spontaneous abortion; mycotoxin; ovarian cancer; reproductive outcome